Transparency indicators to improve accountability for non-profit organizations: a Spanish case study - Moreno-Albarracín, Antonio Luis; Ortega-Rodríguez, Cristina; Licerán-Gutiérrez, Ana; Labella, Álvaro; Martínez, Luis (Technological and Economic Development of Economy, 2021)
We are currently witnessing the development of a set of organizations that have been entrusted with meeting the very diverse needs of citizens. As a result, they receive funds, in order to ensure they are managed appropriately. The transparency of the information revealed by Non-profit Organizations (NPOs) has become of increasing interest to public authorities and research. However, very few studies empirically measure the extent of transparency in NPOs. Only a handful checked the compliance of various indicators, lacking agreement on which ones to include and their weighting. To address this issue, this study empirically validates the weighting of the indicators from the alliance between the Platform for Social Action NGO and the Spanish Coordinator for Development NGO (CONGDE) document with experts in NPOs’ opinions. We use the Best-Worst Method (BWM) to optimally assign weights to multi-criteria decision making situations. Our results show interesting differences in the level of importance given to the indicators by public authorities and experts, suggesting the need for a revision of the importance proposed. First published online 04 May 2021